Contemporary issues with pharmacotherapy for lower urinary tract symptoms. Issue 5 (May 2014) - Osman, N.; Chapple, C. R.
<x xml:space="preserve">Abstract</x> Two articles appeared in the November 2012 edition of the journal evaluating aspects relating to the use of two important pharmacotherapeutic classes for lower urinary tract symptoms (LUTS) in real life clinical practice (1, 2). LUTS is a non‐specific term that encompasses urine storage, voiding and postmicturition symptoms (3). LUTS is a common bothersome problem affecting both men and women with a comparable prevalence in age‐matched patients of both sexes that increases with ageing (4, 5).